2005
DOI: 10.1093/aob/mci168
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the 5S and 45S rDNA Sites and cpDNA Sequence Analysis in Species of the Quadrifaria Group of Paspalum (Poaceae, Paniceae)

Abstract: The subdivision found with FISH is consistent with the clades recovered with cpDNA data and both analyses suggest that the Quadrifaria group, as presently defined, is not monophyletic and its species belong in at least two clades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 41 publications
2
38
0
4
Order By: Relevance
“…Some studies reported the variability of 18S-5.8S-25S rDNA sites and stability of 5S rDNA sites in congeneric species (Adams et al, 2000;Liu et al, 2003;Vaio et al, 2005). Variability of 18S-5.8S-25S rDNA sites was not detected in Japanese and Chinese pear (Yamamoto et al, 2010b), and Toyotomi Nashi.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported the variability of 18S-5.8S-25S rDNA sites and stability of 5S rDNA sites in congeneric species (Adams et al, 2000;Liu et al, 2003;Vaio et al, 2005). Variability of 18S-5.8S-25S rDNA sites was not detected in Japanese and Chinese pear (Yamamoto et al, 2010b), and Toyotomi Nashi.…”
Section: Resultsmentioning
confidence: 99%
“…FISH signals with p Ta 71 do not exhibit variation in size among the different species studied. The presence of these sites in terminal regions of both chromosome arms is frequent in Angiosperms (e.g., Zhang and Sang, 1998;Benko-Iseppon and Morawetz, 2000;Vaio et al, 2005;Urdampilleta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The only general rule to the direction of events is that tetraploids or higher ploidy levels are always derived from diploids or low ploidy levels. Among neopolyploids this assumption has been widely supported by FISH (Linares et al, 1998;Vaio et al, 2005) and GISH (Bennett, 1995), although in some other cases the diploid ancestors are unknown, are extinct or they have diverged since the hybridization/polyploidization event, as in the case of the B genome of common wheat (Petersen et al, 2006) or the D genome of oat (Linares et al, 1998).…”
Section: Chromosome Numbers and The Direction Of Evolutionmentioning
confidence: 98%